Analisis Persepsi Mahasiswa terhadap Penggunaan E-Learning dalam Kurikulum Merdeka di Jurusan Pendidiakn Bahasa Arab FTK UIN Mataram - Lia Dianti; Suparmanto; Auni Islahatun Diniyati; Herawati Herawati; Alisa Muwazanatul Hayati (Al-Mazaya: Jurnal Pendidikan Bahasa Arab, 2024)
This research investigates students' perspectives on E-Learning within the Merdeka Curriculum in the Department of Arabic Language Education at UIN Mataram. Utilizing two questionnaires, the study reveals that the majority of students provided positive responses to E-Learning, although certain aspects require improvement. Evaluation of Zoom Meeting highlights its strengths and challenges, while Google Meet and Google Classroom are explored as alternative options, each with their own advantages and challenges. The research provides a comprehensive overview of students' experiences in distance learning and the applications employed.